Vulnerability of Amazon forests to storm-driven tree mortality. (3rd May 2018) - Negrón-Juárez, Robinson I; Holm, Jennifer A; Marra, Daniel Magnabosco; Rifai, Sami W; Riley, William J; Chambers, Jeffrey Q; Koven, Charles D; Knox, Ryan G; McGroddy, Megan E; Di Vittorio, Alan V; Urquiza-Muñoz, Jose; Tello-Espinoza, Rodil; et al.
Abstract: Tree mortality is a key driver of forest community composition and carbon dynamics. Strong winds associated with severe convective storms are dominant natural drivers of tree mortality in the Amazon. Why forests vary with respect to their vulnerability to wind events and how the predicted increase in storm events might affect forest ecosystems within the Amazon are not well understood. We found that windthrows are common in the Amazon region extending from northwest (Peru, Colombia, Venezuela, and west Brazil) to central Brazil, with the highest occurrence of windthrows in the northwest Amazon. More frequent winds, produced by more frequent severe convective systems, in combination with well-known processes that limit the anchoring of trees in the soil, help to explain the higher vulnerability of the northwest Amazon forests to winds. Projected increases in the frequency and intensity of convective storms in the Amazon have the potential to increase wind-related tree mortality. A forest demographic model calibrated for the northwestern and the central Amazon showed that northwestern forests are more resilient to increased wind-related tree mortality than forests in the central Amazon. Our study emphasizes the importance of including wind-related tree mortality in model simulations for reliable predictions of the future of tropical forests and their effects on the Earth' system.